Flow characterization of a microfluidic device to selectively and reliably apply reagents to a cellular network - Santillo, Michael F. (2007)
A three-dimensional microfluidic device has been successfully fabricated and the flow streams characterized for eventual use in studying communication in an in vitro network of nerve cells. The microfluidic system is composed of two layers of channels: a lower layer for the delivery of pharmacological solutions and an upper layer of channels used to direct the flow of the pharmacological solution streams and perfuse the cells with media and nutrients. Flow profiles have been characterized with computational fluid dynamics simulations, confocal fluorescence microscopy, and carbon-fiber amperometry, which have been used to map changes in flow profiles at different bulk flow rates. Ultimately, the microfluidic system and incorporated cell network will show how networked neurons adapt, compensate, and recover after being exposed to different chemical compounds.